Improving cell-free metabolism through direct integration of artificial respiratory chains - Owen D. Jarman; Nitin Bohra; Peter Claus; Nicole Paczia; Tobias J. Erb (Proceedings of the National Academy of Sciences, 2026)
Energy-conserving mechanisms are essential in supporting cellular life. Yet in synthetic biology, it remains a challenge to reconstruct such processes from the bottom–up and integrate them with other biological functions to create complex systems with life-like properties. Recent efforts to build higher-order cell-free metabolic networks have suffered from the fact that their central oxidation reactions are not coupled to energy conservation, causing kinetic and thermodynamic limitations. Here, we developed an artificial respiratory chain that we tailored to sustain rapid electron transfer in a CO 2 -fixing 16-enzyme catalytic cycle (crotonyl-CoA/ethylmalonyl-CoA/hydroxybutyryl-CoA), while also exploiting the concurrent electron flow for adenosine triphosphate synthesis. We demonstrate how such artificial respiratory chains can be further diversified to accept multiple electron entries and coupled to other biological functionalities, such as cell-free transcription–translation networks. Altogether, our work highlights the opportunities and challenges of directly integrating energy conservation mechanisms when building toward self-sustaining/self-energizing artificial life-like systems.